Comparative Structural Analysis of Magnetic Resonance Neuroimaging in Subjects with Schizophrenia and Schizoaffective Disorder. - Andrade Reyes, María Fernanda; Polito Haro, Francisco; Benito De Celis, Alonso; Osorio Durán, Raúl; Rosel-Vales, Mauricio; Fresán Orellana, Ana; Flores Ramos, Mónica; Saracco-Álvarez, Ricardo Arturo (Salud Mental)
Introduction: Schizoaffective disorder is a complex condition whose clinical manifestations overlap with those of schizophrenia, bipolar disorder, and depression. It is notoriously difficult to diagnose using the DSM-5 and ICD-11. Both the similarities with other diagnoses and the differences between the guidelines of these two diagnostic symptoms hamper its accurate diagnosis. Magnetic resonance imaging, however, is designed to identify specific differences and similarities in brain structures between disorders. Objective: To compare the total intracranial volume, gray matter, white matter, and cerebrospinal fluid in subjects with a schizophrenia or schizoaffective disorder diagnosis using a magnetic resonance imaging database drawn up by the INPRFM. Method: The images of 55 subjects per group (schizophrenia and schizoaffective disorder) were analyzed. The volumetric study was conducted using the CAT12 program for each of the images to obtain the total intracranial volume. The volumes of gray matter, white matter, cerebrospinal fluid, and total volume were compared using a general linear model including sex and group as fixed factors. Results: White matter volume was lower in schizophrenia, with no differences being observed by sex or sex and group interaction. No differences were found between groups in the remaining measurements. Discussion and conclusion: The study provides evidence of general neuroanatomical differences in schizoaffective disorder, supporting the notion that it is not just a variant of schizophrenia, but a clinically and biologically distinct condition.